Handbook of advanced ceramics - Somiya, Shigeyuki (Academic, 2012)
A comprehensive reference for all ceramicists, both in research and working in industry The only definitive reference covering the entire field of advanced ceramics from fundamental science and processing to application Contributions from over 50 leading researchers from around the world This new Handbook will be an essential resource for ceramicists. It includes contributions from leading researchers around the world, and includes sections on: Basic Science of Advanced Ceramic, Functional Ceramics (electro-ceramics and optoelectro-ceramics) and engineering ceramics. Contributions from over 50 leading researchers from around the world Sections on: Basic Science of Advanced Ceramics, Functional Ceramics (Electro-Ceramics and Optoelectro-Ceramics), and Engineering Ceramics Approximately 750 illustrations.
Previous edition: 2003.
Keywords: Ceramics.; elektronické knihy; electronic books